2023
DOI: 10.3390/ijms24087031
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Increases ATX Expression by Histone Crotonylation in a HIF-2α-Dependent Manner

Abstract: Autotaxin (ATX), the key enzyme that generates lysophosphatidic acid (LPA) from lysophosphatidylcholine (LPC), is involved in tumorigenesis through the ATX-LPA axis and is regarded as a valuable target in tumor therapy. Hypoxia is a major feature of solid tumors and contributes to tumor development with striking alterations in the gene expression profile. Here, we show that hypoxia induces ATX expression in a hypoxia-inducible factor (HIF) 2α-dependent fashion in human colon cancer SW480 cells. HIF-2α is direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Liao M et al reported the relationship between histone H3K27 crotonylation and DNA damage of colon cancer ( Liao et al, 2022 ). Qu M et al revealed a novel mechanism of histone crotonylation-mediated ATX expression regulation by in a HIF-2α-dependent manner in a colon cancer SW480 cells ( Qu et al, 2023 ). Compared with the three researches, we find a new crotonylated protein RRM2, which K283 site crontonylation contributes to cisplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liao M et al reported the relationship between histone H3K27 crotonylation and DNA damage of colon cancer ( Liao et al, 2022 ). Qu M et al revealed a novel mechanism of histone crotonylation-mediated ATX expression regulation by in a HIF-2α-dependent manner in a colon cancer SW480 cells ( Qu et al, 2023 ). Compared with the three researches, we find a new crotonylated protein RRM2, which K283 site crontonylation contributes to cisplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The level of nonhistone ENO1-Kcr is elevated in colorectal cancer tissues, and ENO1 K420Cr has been shown to stimulate the growth, migration and invasion of colorectal cancer cells in vitro ( Hou et al, 2021b ). Qu ( Qu et al, 2023 ) et al reported that p300/CBP-mediated Kcr plays a role in the induction of hypoxia by ATX in SW480 cells. Liao ( Liao et al, 2022 ) et al reported a decrease in the level of H3K27cr, which may be facilitated by SIRT6 during DNA damage in colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…LPAR5 also interacts with cannabinoid receptor 2 (CB2) to activate AKT signalling and subsequently induce migration and proliferation [92]. Hypoxic colon cancer cells activate HIF2α, which binds hypoxia response elements (HREs) in the ATX promoter to induce the upregulation of ATX expression by histone H3 crotonylation and promote cell migration [93]. Non-alcoholic steato-hepatitis (NASH) is a condition that can promote the development of liver tumours.…”
Section: Lpa In Other Tumour Typesmentioning
confidence: 99%